Rimbo: Hutan Bagi Orang Rimba di Taman Nasional Bukit Dua Belas - Ulfah Fauziah (Balale' : Jurnal Antropologi, 2022)
The tropical rain forest area in Sumatra is not spared from extensive exploitation that has undergone changes in the last decade. The impact of degradation caused by the exploitation of oil palm land and large-scale clearing and widespread fires has caused the forest to be depleted. The depletion of the forest has disturbed the local community in it, namely the Orang Rimba who have been inhabiting lowland forests in the TNBD (Bukit Dua Belas National Park) area.This study uses an ethnoecological approach to describe and explain the Orang Rimba knowledge system to the forest, the relationships built for survival and the importance of the forest and the survival of the Orang Rimba.This research shows that Rimbo is a place and living space for Orang Rimba. So there is a classification of Rimbo for Orang Rimba which divides it into two, namely Jungle/Forest (Rimbo) and Tana (Land). The forest is divided into Rimbo, Bungaron, Ranah, Sesap and Belukah, Benuaron, Lalot'on. Meanwhile, Tana is divided into Tana Dewo, Tana Pasuron and Tana Bediom and Tana Perano'an and Ladong. On the basis of the division of Rimbo, the Orang Rimbo refer to their belief that nature is divided into Halom Nio and Halom Dewo. So for the Orang Rimba, Rimbo is a culture and survival in carrying out life.